2000
DOI: 10.1161/01.atv.20.11.2441
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase (PON1) Phenotype Is a Better Predictor of Vascular Disease Than Is PON1 192 or PON1 55 Genotype

Abstract: Abstract-The paraoxonase (PON1) PON1-Q192R and PON1-L55M polymorphisms have been inconsistently associated with vascular disease. Plasma PON1 activity phenotypes vary markedly within genotypes and were, therefore, expected to add to the informativeness of genotype for predicting vascular disease. The case-control sample included 212 ageand race-matched men (mean age 66.4 years). The 106 carotid artery disease (CAAD) cases had Ͼ80% carotid stenosis, and the 106 controls had Ͻ15%. [15][16][17] The cardioprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
228
3
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 293 publications
(241 citation statements)
references
References 46 publications
8
228
3
2
Order By: Relevance
“…Thus, it is likely that paraoxon and phenylacetate seemed to be better surrogate substrates than diazoxon for measuring PON1 activity. Jarvik et al (2000) found that the PON1 activity towards diazoxon was more predictive of vascular disease status than was the PON1 activity towards paraoxon in marginal analysis. However, in the only prospective study published so far, paraoxon but not diazoxon hydrolysis was an independent risk factor for CHD events (Mackness et al 2003).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, it is likely that paraoxon and phenylacetate seemed to be better surrogate substrates than diazoxon for measuring PON1 activity. Jarvik et al (2000) found that the PON1 activity towards diazoxon was more predictive of vascular disease status than was the PON1 activity towards paraoxon in marginal analysis. However, in the only prospective study published so far, paraoxon but not diazoxon hydrolysis was an independent risk factor for CHD events (Mackness et al 2003).…”
Section: Discussionmentioning
confidence: 93%
“…These standards showed less than 8% variability between independent assays. An additional 26 samples from a previously determined PON1 status frequency distribution of known phenotypes and genotypes (Jarvik et al, 2000) were included as additional standards for CPOase assays. There was a mean 4.4% variation between assays for these 29 samples.…”
Section: Pon1 Inferred Genotype and Chlorpyrifosoxonase Activitymentioning
confidence: 99%
“…57,58 Unfortunately, paraoxonase activity is calcium dependent and cannot be measured in the plateletrich plasma we have collected from our entire sample. We have thus begun assessing paraoxonase, diazoxonase, and arylesterase activity in all 217 serum samples currently available from the AGRE collection, 30 including 40 families with one or more autistic patients and their first-degree relatives.…”
Section: Markersmentioning
confidence: 99%